The impact of regional poverty on public health expenditure efficacy across South Africa’s provinces: investigating the influence of historical economic factors on health - Dlamini, Msawenkosi; Mbonigaba, Josue (Frontiers in Public Health, 2024)
Introduction/objectivesMore than half of South Africa’s population lives in poverty, with significant health disparities across different regions. This study investigates the effects of regional poverty and historical economic factors on the efficacy of public health expenditure to understand how socioeconomic contexts influence overall public health outcomes.MethodsOur study utilized annual data from 2005 to 2019 for 9 provinces, drawing from the General Household Survey, Health Systems Trust database, and National Treasury’s Intergovernmental Fiscal Review. The primary health outcome was life expectancy at birth, while public health expenditure per capita was the main independent variable. We developed the Provincial Index of Multiple Deprivation to assess poverty, incorporating dimensions such as health, education, and living standards. We employed a two-way fixed effects model to examine the complex relationships between regional poverty, public health spending, and health outcomes.ResultsThe study found that poverty levels moderate the impact of public health spending on health outcomes, as evidenced by varying results across different provincial regions. Health outcomes in poorer provinces were less influenced by public health spending than wealthier regions. Additionally, the study established that income per capita, along with its lagged values and the lagged values of public health expenditure per capita, did not significantly affect health outcomes as measured by life expectancy.Conclusion/recommendationsThe impact of health expenditure in South Africa is influenced by regional poverty levels. To maximize the effectiveness of health spending, equitable, region-specific interventions tailored to address the unique health challenges of each area should be implemented.